A research strategy for environmental, health, and safety aspects of engineered nanomaterials (National Academies Press, 2012)
The nanotechnology sector, which generated about $225 billion in product sales in 2009, is predicted to expand rapidly over the next decade with the development of new technologies that have new capabilities. The increasing production and use of engineered nanomaterials (ENMs) may lead to greater exposures of workers, consumers, and the environment, and the unique scale-specific and novel properties of the materials raise questions about their potential effects on human health and the environment. Over the last decade, government agencies, academic institutions, industry, and others have conducted many assessments of the environmental, health, and safety (EHS) aspects of nanotechnology. The results of those efforts have helped to direct research on the EHS aspects of ENMs. However, despite the progress in assessing research needs and despite the research that has been funded and conducted, developers, regulators, and consumers of nanotechnology-enabled products remain uncertain about the types and quantities of nanomaterials in commerce or in development, their possible applications, and their associated risks. A Research Strategy for Environmental, Health, and Safety Aspects of Engineered Nanomaterials presents a strategic approach for developing the science and research infrastructure needed to address uncertainties regarding the potential EHS risks of ENMs. The report summarizes the current state of the science and high-priority data gaps on the potential EHS risks posed by ENMs and describes the fundamental tools and approaches needed to pursue an EHS risk research strategy. The report also presents a proposed research agenda, short-term and long-term research priorities, and estimates of needed resources and concludes by focusing on implementation of the research strategy and evaluation of its progress, elements that the committee considered integral to its charge.